Screening for Moral Injury: The Moral Injury Symptom Scale – Military Version Short Form. Issue 11 (26th March 2018) - Koenig, Harold G; Ames, Donna; Youssef, Nagy A; Oliver, John P; Volk, Fred; Teng, Ellen J; Haynes, Kerry; Erickson, Zachary D; Arnold, Irina; O'Garo, Keisha; Pearce, Michelle
Abstract: Introduction: To develop a short form (SF) of the 45-item multidimensional Moral Injury Symptom Scale – Military Version (MISS-M) to use when screening for moral injury and monitoring treatment response in veterans and active duty military with PTSD. Methods: A total of 427 veterans and active duty military with PTSD symptoms were recruited from VA Medical Centers in Augusta, GA; Los Angeles, CA; Durham, NC; Houston, TX; and San Antonio, TX; and from Liberty University, Lynchburg, Virginia. The sample was randomly split in two. In the first half ( n = 214), exploratory factor analysis identified the highest loading item on each of the 10 MISS scales (guilt, shame, moral concerns, loss of meaning, difficulty forgiving, loss of trust, self-condemnation, religious struggle, and loss of religious faith) to form the 10-item MISS-M-SF; confirmatory factor analysis was then performed to replicate results in the second half of the sample ( n = 213). Internal reliability, test–retest reliability, and convergent, discriminant, and concurrent validity were examined in the overall sample. The study was approved by the institutional review boards and the Research & Development (R&D) Committees at Veterans Administration medical centers in Durham, Los Angeles, Augusta, Houston, and San Antonio, and the Liberty University and Duke University Medical Center institutional review boards. Findings: The 10-item MISS-M-SF had a median of 50 and a range of 12–91 (possible range 10–100). Over 70% scored a 9 or 10 (highest possible) on at least one item. Cronbach's alpha was 0.73 (95% CI 0.69–0.76), and test–retest reliability was 0.87 (95% CI 0.79–0.92). Convergent validity with the 45-item MISS-M was r = 0.92. Discriminant validity was demonstrated by relatively weak correlations with social, religious, and physical health constructs ( r = 0.21–0.35), and concurrent validity was indicated by strong correlations with PTSD, depression, and anxiety symptoms ( r = 0.54–0.58). Discussion: The MISS-M-SF is a reliable and valid measure of MI symptoms that can be used to screen for MI and monitor response to treatment in veterans and active duty military with PTSD.